Survival rate and prognostic factors of surgically resected clinically synchronous multiple primary non-small cell lung cancer and further differentiation from intrapulmonary metastasis - Xiao, Fei (J Thorac Dis, 2017)
BACKGROUND: The diagnosis, staging, and therapeutic strategy for synchronous multiple primary non-small cell lung cancer (SMP-NSCLC) remain unclear. Distinguishing SMP-NSCLC from intrapulmonary metastasis is difficult but of great importance for selecting the surgical procedure and prognoses. METHODS: Fifty-two patients diagnosed with SMP-NSCLC according to the modified Martini-Melamed criteria in the thoracic surgery department of the China-Japan Friendship Hospital from November 2004 to December 2015 were enrolled in this retrospective study. A total of 106 tumors were subjected to pathological examination. Close follow-up and survival analysis were performed. RESULTS: The perioperative morbidity rate was 5.8%, with no cases of perioperative death. The overall 5-year survival rate was 40.6%, the cancer-specific 5-year survival rate was 54.5%, and the median survival time was 52 months. Older age (P=0.553), sex (P=0.600), smoking history (P=0.496), tumor distribution (P=0.461), video-assisted thoracoscopic surgery (VATS) (P=0.398), and adjuvant chemotherapy (P=0.078) did not affect survival. Preoperative percentage of forced expiratory volume in the first second (P=0.022), Charlson comorbidity index (P=0.034), surgical procedure (P=0.040), and highest pT stage (P=0.022) were independent risk factors in the multivariate analysis. Different pathological subtypes were identified in 13 of 18 cases of multiple adenocarcinomas. Different gene mutation types and correlations between tumors were identified through NGS in those with the same pathological subtype. CONCLUSIONS: Postoperative survival rates in SMP-NSCLC were satisfactory. Non-radical resection might improve the prognosis for patients with a tolerable general condition and pulmonary function. Higher pT stage might result in poorer survival rates. Larger sample size and future study are still needed to identify the prognostic factors. Comprehensive histologic assessment and next generation sequencing (NGS) could be effective methods for screening SMP-NSCLC.